Is gluten free and casein free (GFCF) diet effective for individuals with autism? (Medical Journal of Indonesia, 2011)
Background: Even though the etiology of autistic spectrum disorder (ASD) has not been clearly known, various types of therapies have been offered. One of the most popular therapies is Gluten Free and Casein Free Diet - GFCF diet. Methods: A structured internet literature search was conducted using Pubmed and Cochrane library. Titles and abstracts were screened using predetermined selection criteria. Critical appraisal was conducted based on standardÂ criteria for relevance, validity, and levels of evidence. Results: Based on relevance, only four out of twelve selected articles can be used; one is a systematic review and three randomized controlled trials (RCTs). Several methodological problems which could lead to over-estimation of the effect were found in the studies including poor randomization and selective drop-out. Risk of under-estimation of report due to small number of participants and in-adequate duration of intervention was also found. Small to moderate improvement were found in some outcome measured including overall autistic traits, social isolation, and the abilit in communication and interaction. However, insignificant differences also found in some area such as individual's behavior, cognitive and motor function. Conclusion: Available studies fail to provide sufficiently credible and strong evidence to recommend the practice of GFCF diet in treating autism. (Med J Indones 2011; 20:114-8)